Emotional and Spiritual Intelligence of Children in Coastal Areas - Toryeh, Tacha; M. Suud, Fitriah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to determine the emotional and spiritual intelligence of children who live side by side with prostitutes. This study used a qualitative method with a case study approach. Data collection techniques consisted of observation and interviews. The results stated that the emotional and spiritual intelligence of children who live side by side with prostitutes tends to be lacking. They tend to imitate the habits found in the environment. This study presents data on the causes and effects of the lack of emotional and spiritual intelligence in children so that it can be used as a reference for parents who have an important role in improving children's emotional and spiritual intelligence, especially for those who live in environments that are less conducive to children's growth and development. In addition, this study can be used as a basic reference for researchers who are interested in emotional and spiritual intelligence in children who live in areas with prostitutes.